Serum N-Terminal Pro-B-Type Natriuretic Peptide Level is Negatively Associated with Vascular Reactivity Index by Digital Thermal Monitoring in Patients with Hypertension - Chien-Hao Hsiao; Chiu-Fen Yang; Ji-Hung Wang; Bang-Gee Hsu (Reviews in Cardiovascular Medicine, 2024)
Background: B-type natriuretic peptide (BNP) coordinates endothelial homeostasis and remodeling, with endothelial dysfunction associated with cardiovascular mortality in the general population without heart failure. The objective of this study was to investigate the correlation between serum N-terminal pro-B-type natriuretic peptide (NT-pro-BNP) levels and endothelial dysfunction among patients diagnosed with hypertension. Methods: This cross-sectional, single-center study included 90 patients with hypertension. An electrochemiluminescence immunoassay measured NT-pro-BNP levels, and a digital thermal monitoring device calculated a vascular reactivity index (VRI) as a measurement for endothelial function. In this study, VRI < 1.0 denoted poor vascular reactivity, 1.0 ≤ VRI < 2.0 indicated intermediate vascular reactivity, and a VRI ≥ 2.0 suggested good vascular reactivity. Results: Out of all the hypertensive patients, eight (8.9%) displayed poor vascular reactivity (VRI < 1.0), while 39 (43.3%) exhibited intermediate vascular reactivity (1.0 ≤ VRI < 2.0), leaving the remaining 43 patients demonstrating good vascular reactivity. Older age (p = 0.012) and elevated serum NT-pro-BNP levels (p < 0.001) were found to be associated with poorer vascular reactivity. Older age (r = –0.221, p = 0.036) and log-transformed serum levels of NT-pro-BNP (log-NT-pro-BNP, r = –0.505, p < 0.001) exhibited a negative correlation with VRI values in patients with hypertension. Following a multivariate linear regression test, serum log-NT-pro-BNP level (β = –0.505, adjusted R2 change = 0.246, p < 0.001) emerged as being significantly and independently associated with VRI values among hypertensive patients. Conclusions: In patients with hypertension, there was a negative association observed between serum log-NT-pro-BNP levels and endothelial dysfunction determined by VRI values.